Integration of an aminopyridine derived cobalt based homogenous cocatalyst with a composite photocatalyst to promote H2 evolution from water. (12th March 2021) - Irfan, Rana Muhammad; Khan, Sayed Ali; Tahir, Mudassir Hussain; Ahmad, Tauqeer; Ali, Liaqat; Afzal, Masood; Ali, Hazrat; Abbas, Anees; Munawar, Khuram Shahzad; Zhao, Jianqing; Gao, Lijun
Abstract : Molecular cocatalysts are promising materials to improve the performance of photocatalytic systems. Abstract : Inexpensive cocatalysts are promising materials to improve the performance of photocatalytic systems. However, a cocatalyst can be anchored onto a photosensitizer in certain amount and further loading can hinder the visible light by blocking the active sites of the photosensitizer. Herein, we introduce the utilization of a cobalt based homogenous cocatalyst with composite photocatalyst CdS/Ni3 C. The homogenous cocatalyst did not occupy the physical space on the photosensitizer and the performance of CdS/Ni3 C was significantly enhanced from 263 μmol h −1 to 750 μmol h −1 . The present study showed that homogenous cocatalysts paved a way to further capture the electrons from photoexcited composite photocatalysts and have great potential to enhance the photocatalytic performance for low cost H2 evolution under visible light.